Forces behind Entrepreneurship of Women- an Economic Study - Mani, C. (International Journal of Bio-resource and Stress Management, 2011)
Entrepreneurship seems to be ideal for women seeking participation in the country’s economic development because of certain factors. Emergence of entrepreneurship is considered to be closely linked to social, cultural, religious and psychological variables. Changes seem to have become acceptable norms in the context of women at work in the Indian situation today with more and more women participating in the economic development. This study discusses the socio-economic background of the selected women entrepreneurs in Tirunelveli district, Tamilnadu state, India. Further, the psychological factors such as personality traits comprising confidence, optimism, independence and the like have also been examined. 300 entrepreneurs were selected for primary data collection by adopting simple random sampling method. The reference period of survey was 2009-10. The analysis of χ² results indicated that the socio, economic profile variables, except caste, type of family and material possession have significant association with entrepreneurship. The correlation analysis showed that the relationship between entrepreneurship and personality variables namely decision making ability, economic motivation, managerial ability, problem recognition and risk taking willingness was significant.